Pengaruh Job Description Dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Melalui Motivasi Kerja Sebagai Variabel Mediasi Pada PT. Indofood Cbp Sukses Makmur Tbk Cibitung - Lisa Andriani; Fitri Rezeki (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The decline in employee productivity of PT Indofood CBP Sukses Makmur Tbk Cibitung in 2023 is allegedly influenced by job description factors and employee work discipline. This study aims to analyze the effect of job description and work discipline on employee work productivity with work motivation as a mediating variable. The type of research used is explanatory with a quantitative approach. Data collection was carried out through questionnaires on 90 employees as samples with saturated sampling techniques. Data analysis was performed using SmartPLS 3.3.9 statistical methods. The results showed that job description, work discipline, and work motivation had a positive and significant influence on employee work productivity. Job description and work discipline also have a positive and significant effect on work motivation, which then acts as a mediator between the two variables with work productivity. The company needs to pay attention to job descriptions and maintain employee discipline to increase work productivity. For future research, it is recommended to combine other factors that can affect work productivity directly or indirectly, as well as conduct longitudinal research to observe changes in phenomena over time.